Hypocretin (orexin) deficiency predicts severe objective excessive daytime sleepiness in narcolepsy with cataplexy - Baumann, C R; Khatami, R; Werth, E; Bassetti, C L (Journal of neurology, neurosurgery and psychiatry, 2006)
Cerebrospinal fluid (CSF) hypocretin-1 deficiency is associated with definite (“clear cut”) cataplexy in patients with narcolepsy. The relationship between CSF hypocretin-1 levels and other narcoleptic symptoms (including excessive daytime sleepiness, EDS) is not properly understood. In a consecutive series of 18 subjects with narcolepsy and definite cataplexy, patients with undetectable CSF hypocretin-1 (n = 12) were found to have significantly lower mean sleep latencies (p = 0.045) and a higher frequency of sleep onset REM periods (SOREMPs, p = 0.025) on multiple sleep latency test than patients (n = 6) with detectable levels. Conversely, Epworth sleepiness scale scores, the frequency of hallucinations/sleep paralysis, and the frequency and severity of cataplexy were similar in both groups. These results suggest that hypocretin deficiency identifies a homogenous group of patients with narcolepsy characterised by the presence of definite cataplexy, severe EDS, and frequent SOREMPs.